THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS, WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE AT THE DISTRICT OFFICES OF JEBRES, PASAR KLIWON, LAWEYAN AND BANJARSARI IN SURAKARTA CITY - Nadela Ajeng Widyaningrum; M. Farid Wajdi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
The purpose of this research is to analyze the influence of individual characteristics, work environment and motivation on employee performance at the Jebres, Pasar Kliwon, Laweyan and Banjarsari District offices in Surakarta City. This research method is using quantitative. The type of data used in the study is primary data. The population of this research is all employees at the Jebres, Pasar Kliwon, Laweyan and Banjarasari District offices in Surakarta City. The sample technique used in this study was purposive sampling. The number of samples in this study were 72 respondents. The method used for data collection is the questionnaire method. The data analysis technique used in this research is SEM PLS using Smart PLS tools. The results of this study are Individual characteristics do not have a significant effect on Employee Performance. Work Environment has a positive and significant influence on Employee Performance. Motivation has a positive and significant influence on Employee Performance